Art during the Reign of Rudolf II as Quintessence of Leading Mannerism Trend at Prague Art Center - Romanenkova, Julia; Bratus, Ivan; Kuzmenko, Halyna; Streltsova, Svitlana (Journal of History Culture and Art Research, 2020)
This article is devoted to Rudolfine art as one of the style-forming components and a significant trend in European Mannerism of the 16-17th centuries. A general overview of this style, necessary preconditions that led to its emergence in the artistic culture of Europe, Mannerism major trends and its vectors of spreading in Europe, the role of Rudolfine artists in this process, are laid out in this work. We emphasized the lack of adequate research made in the field of Art History. The personal influence of Emperor Rudolf II on the formation of court art at that time was pointed out. We looked into the background and circumstances at which the Prague Art Center was established by the Emperor and how he provided patronage to the arts and science. The importance of works by prominent artists of the Rudolfine era who worked at the Prague Art Center is highlighted. The main directions of Mannerism distribution through European countries, mainly its further adaptation and style transformation depending on the geographical location, grounds on why the art was so influenced by the Italian movement, the approach and tools of Mannerism in one of the leading European courts. The main characteristics of the Rudolfine art style is highlighted. Its main representatives are defined and their individual creative styles are separately analyzed, including Giuseppe Arcimboldo, Roelant Savery, Bartholomeus Spranger, Joris Hoefnagel, Adriaen de Vries, Joseph Heintz the Elder, and Hans von Aachen. It is pointed out that there was a tendency in the synthesis of Italian, French, and German trends which formed the foregrounds of individual styles of major representatives in Rudolfine art that have been a significant element of Mannerism. General characteristics of stylistic features of Rudolfine artists as representatives of Mannerism who contributed to its fast proliferation in Europe are laid out.